Faktor yang Memengaruhi Financial Performance pada Perusahaan Manufaktur dengan Peringkat PROPER - Billyaprianto, Virginia Putri; Widyasari, Widyasari (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This study aims to obtain empirical evidence of the effect of Corporate Social Responsibility, Good Corporate Governance, Environmental Performance and company size on the company's Financial Performance. This study uses secondary data obtained from the Indonesia Stock Exchange (IDX) and processed using the Econometrics Vies (Eviews) version 12 program and Microsoft Excel 2018. The population in this study are manufacturing industrial companies listed on the Indonesia Stock Exchange in the 2017-2019 period which were PROPER participants during 2017-2019. The results of the study found that there was a positive and significant effect of the variables of social responsibility and company size on the company's Financial Performance. However, the study did not find any significant effect of the variables of corporate governance and environmental performance on the company's Financial Performance.